The Dominant Factors Affecting the Dietary Habits Among School-Age Children Utilizing the Dorothea Orem Theory Approach at Orphanages Surabaya - Gita Marini; Fatma Sriardiana; Yuanita Wulandari; Supatmi Supatmi (STIKep PPNI Jawa Barat, 2023)
Aims: The diets of foster children in orphanages in groups tend to differ from those of children cared for by their parents. Indeed, applying Self Care Theory to children will help train them in independence in meeting their needs. However, there is a lack of studies to explore the factors affecting children's diets utilizing Dorothea Orem's theory approach. Objective: Analyzing the dominant factors affecting school-age children's eating patterns utilizing Dorothea Orem's theory approach at the Muhammadiyah Orphanage in Surabaya. Methods: A cross sectional design included 43 children with orphanages in Surabaya with Cluster Random Sampling technique. The dependent variable is dietary habits. At the same time, the independent variables in this research include nutritional knowledge, body image, the role of caregivers, and food availability. The Spearman-Rho with a significant value <0.05 was performed. Results: Results of the study revealed that age (p = 0.007), caregiver role (p = 0.012) and food availability (p = 0.000) was significantly correlated with dietary habits. However, gender (p = 0.930), nutritional knowledge (p = 0.667), body image (p = 0.975) no significantly correlated with dietary habits. Conclusion: Food availability is the most vital factor and directly influences the diet of school-age children. Moreover, in this case, the foster mother and adequate food availability support the child’s independence process in fulfilling the appropriate self-care process.